The Implementation Of Teaching Learning Process Of English At Sd Islam Hidayatullah Banyumanik Semarang (An Ethnography Study) - Martopo, Ruliana (2004)
This research paper aims is to observe the implementation of teaching learning process of English. The research was conducted at SD Islam Hidayatullah Banyumanik Semarang, Jl. Durian Selatan I / 6 Srondol Wetan Banyumanik Semarang in academic year 2003/2004. The problem of the study is how is the implementation of the teaching learning process of English at SD Islam Hidayatullah is conducted and the strengths and weaknesses there. The objective of this research is to know and describe with ethnography view the teaching learning process of English at SD Islam Hidayatullah in some dimensions. The data used in this research are derived from event, informant, and document. There are fourth techniques in collecting the data namely: observation, interview, questionnaire, and document analysis. Based on the data analysis the findings of the research are, the implementation of teaching learning process of English at SD Islam Hidayatullah Banyumanik Semarang is divided into seven sections; (1) The English teaching objective which consists of general and specific objective. (2) The syllabus model. The syllabus in this research is topic and grammar syllabus. (3) The classroom activities. There are discussions on what activities that the teacher uses in the teaching learning process in the classroom. (4) The classroom procedures. There are discussions on the teaching learning process in the classroom. (5) The teacher's role. It covers the function of the teacher when they do the work as a teacher. (6) The learner's role. It describes the students' responsibility as a learner. And (7) Evaluation. It describes the type and procedure of evaluation used in the English teaching learning process. Finally, the writer found that the implementation of the teaching learning process of English at SD Islam Hidayatullah is also has strengths and weaknesses. The strengths are the objective of the English teaching learning process, the material, and the classroom procedure. The weaknesses are the schedule and the classroom activity